PERANCANGAN MESIN PICK TO LIGHT PADA STATION PACKING DI PT. XYZ - Tambunan, Yopi Partomuan; Sirait, Ganda (Computer Science and Industrial Engineering, 2023)
At the packing station, the automation system that can be used is the pick to light system. Pick to light is a paperless picking system designed to simplify the order fulfillment and picking process, or the packing process. Pick to light offers an innovative and efficient solution, thus improving efficiency, productivity, and picking accuracy, while saving costs. The research method uses a way by identifying problems, determining the formulation of problems, knowing the objectives of the research, supported by a theoretical basis, then collecting data by interview and observation, then designing the machine with the NIDA method. The result of this research is the creation of a machine that can reduce the Missing Process in the product packaging process, with the NIDA method as a guide, then complaints are found from operators who work in the product packaging process, then researchers develop these complaints to get needs. Based on the research that has been carried out by researchers on the product packaging process, it can be concluded that the machine that has been designed, namely the pick to light machine, can reduce the missing process. not only reduce, this machine also turns out to be able to prevent missing processes.